Las edades de la República - Lara Campos Pérez (Cahiers de Civilisation Espagnole Contemporaine)
This article reflects on visual representation of life´s cycle metaphor in order to explain the political ocurrences in Spanish Second Republic. To do this, we focus in the different age sectors in which was presented the allegorical figure identified with the Republic, as well as the various meanings attributed to each one. The analysis was made from six newspaper cartoons, from different ideological positions, allowing appreciate the richness and plasticity of both the metaphor itself as the political symbol used to embody. The main objective is to understand and value the usefulness of this metaphor in Spain in the 30s and clarify the meaning of his contributions to political languages; this in a context unquestionably influenced by the huge boom that political imagination experienced during interwar period.